2007
DOI: 10.1007/s10517-007-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of the efficiency of climatotherapy in patients with chronic heart failure

Abstract: We studied the dependence of climatotherapy effectiveness in patients with chronic heart failure (functional classes 0-II) on Ca(2+)-ATPase, phospholamban, beta1-adrenoceptor, and insulin-like growth factor 1 gene polymorphisms and possible interaction of these genes during the realization of the effect of climatotherapy. The effectiveness of climatotherapy depended on polymorphism of the studied genes; the maximum effect was attained in patients with the GG polymorphism of the Ca(2+)-ATPase gene, GT polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…Indeed, an increasing number of polymorphisms and mutations in signaling components regulating cardiac contractile function have been found to be linked to dilated cardiomyopathy or propensity to arrhythmias [17,18,19,20,21]. For example, multiple human polymorphisms on adrenergic signaling pathways have been reported to be direct or conjunct factors affecting development, prognosis or therapy of heart failure [17,22,23,24,25]. PP1 inhibitor-1 has recently emerged as an important regulator for cardiac contractile function by maintaining an appropriate phosphorylation level of cardiac proteins and serving as a downstream mediator in the β-adrenergic signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increasing number of polymorphisms and mutations in signaling components regulating cardiac contractile function have been found to be linked to dilated cardiomyopathy or propensity to arrhythmias [17,18,19,20,21]. For example, multiple human polymorphisms on adrenergic signaling pathways have been reported to be direct or conjunct factors affecting development, prognosis or therapy of heart failure [17,22,23,24,25]. PP1 inhibitor-1 has recently emerged as an important regulator for cardiac contractile function by maintaining an appropriate phosphorylation level of cardiac proteins and serving as a downstream mediator in the β-adrenergic signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Разработаны мето-ды расчета биоклиматических показателей и их рай-онирования, физиологические принципы санитар-но-климатического районирования территорий, са-наторно-курортной реабилитации населения, ис-следованы проблемы акклиматизации населения в различных климатических условиях, механизмы физиологического и лечебного воздействия климата и погоды на организм человека и его жизнеобеспе-чение [21,22]. Проведенные в различных климати-ческих зонах России исследования по адаптации организма человека к неблагоприятным условиям среды позволили разработать систему расчета и оценки погодных условий с учетом сезонных коле-баний и изменчивости основных гелиометеороло-гических факторов.…”
Section: российская научная школа климатотерапииunclassified
“…Moreover, randomised controlled studies on clinical effects (Schuh 1993;de Andrade et al 2008;Harari et al 2007;Hodak et al 2003;Wolf et al 2003b;Cohen et al 2005;Autio et al 2002) and relevant factors (Cohen et al 2008;Uosif et al 2008;Kovlen et al 2007;Nissen et al 1998) are available within this area. For treatment in specific climatic regions, scientific studies have shown beneficial effects in various health conditions (Kragballe et al 1996;Gutenbrunner et al 2007;Sukenik et al 1990aSukenik et al , 1990bSukenik et al , 1994Sukenik et al , 1995Paran et al 1998;Sukenik 1998;Buskila et al 2001;Neumann et al 2001) Use of other therapeutic factors A description of the use of other therapeutic factors is beyond the framework of this paper.…”
Section: Use Of Climatic Factorsmentioning
confidence: 99%